1989
DOI: 10.1123/ijsb.5.4.403
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Interactions in a Two-Segment Kinetic Chain. Part I: General Model

Abstract: The motion of a body segment is determined by joint torques and by the motions of the segments proximal or distal to it. This paper describes a three-dimensional model that was used to determine the effects of the shoulder and elbow joint torques and of the upper trunk and arm motions on the angular accelerations of the arm segments during baseball pitching. Equations were developed to fractionate the three-dimensional components of the angular acceleration vector of each segment into angular acceleration term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 19 publications
0
68
1
Order By: Relevance
“…Although many studies in 3D kinetics have investigated the profiles of the resultant joint torque during walking and running (Aleshinsky and Zatsiorsky, 1978;Apkarian et al, 1989;Eng and Winter, 1995;Glitsch and Baumann, 1997;Kim and Eng, 2004) and sports movements such as throwing and kicking (Bahamonde and Knudson, 2003;Elliott et al, 2003;Feltner, 1989;Feltner andDapena, 1986, 1989;Fleisig et al, 1995Fleisig et al, , 1999Nunome et al, 2002), only a few studies have examined the interaction torque during 3D movements (Feltner and Dapena, 1989;Hong et al, 2001;Kadota et al, 2004). There are two differences between the interaction torque analysis method presented by the abovementioned authors and our method.…”
Section: Discussioncontrasting
confidence: 49%
“…Although many studies in 3D kinetics have investigated the profiles of the resultant joint torque during walking and running (Aleshinsky and Zatsiorsky, 1978;Apkarian et al, 1989;Eng and Winter, 1995;Glitsch and Baumann, 1997;Kim and Eng, 2004) and sports movements such as throwing and kicking (Bahamonde and Knudson, 2003;Elliott et al, 2003;Feltner, 1989;Feltner andDapena, 1986, 1989;Fleisig et al, 1995Fleisig et al, , 1999Nunome et al, 2002), only a few studies have examined the interaction torque during 3D movements (Feltner and Dapena, 1989;Hong et al, 2001;Kadota et al, 2004). There are two differences between the interaction torque analysis method presented by the abovementioned authors and our method.…”
Section: Discussioncontrasting
confidence: 49%
“…A previous study analysed motion-dependent angular acceleration of the throwing forearm [8]. Although their model decomposed the joint angular acceleration into the inertial angular acceleration-, velocity-, and linear acceleration-dependent components of the proximal and distal segments, the model was not able to quantify the elbow extension/flexion angular acceleration due to the multijoint actions of the throwing arm and trunk because the two-segment simple model was used.…”
Section: Discussionmentioning
confidence: 97%
“…Feltner and Dapena [8] analysed the motion-dependent interactions between the throwing upper arm and forearm in baseball pitching. That study showed that the rapid elbow extension that occurred before ball release was primarily generated by the upper arm motion-dependent torque (due primarily to the rotation of the trunk), and not by the elbow extensor torque.…”
Section: Introductionmentioning
confidence: 99%
“…Although several researchers have tried to reveal its kinetic mechanism by using the equations of motion (Feltner, 1989;Feltner and Dapena, 1989;Hirashima et al, 2003Hirashima et al, , 2007bHong et al, 2001;Putnam, 1991Putnam, , 1993, no study has accurately assessed the effect of the velocity-dependent torque on the joint angular accelerations. These studies dealt with the equation of each segment separately, and considered that each joint angular acceleration can be explained by the joint torque, gravity torque, and interaction (motion-dependent) torque.…”
Section: Introductionmentioning
confidence: 99%